The Clinical Dilemma of Autism Spectrum Disorder Diagnosis in a Child with 9p Deletion - Karba, Brendan E.; Lemay, Jean-Francois; McLeod, Scott A. (Journal of Pediatric Genetics, 2020)
We reported on a 3-year-old girl child patient with the presence of trigonocephaly, broad nasal bridge, flattened occiput, and midface hypoplasia. Formal assessment of her development profile demonstrated expressive and receptive language delays, fine and gross motor delays, and no imaginative or symbolic representative play. Investigation of the etiology of her developmental delays revealed a genetic diagnosis of a 9p24 deletion by chromosomal microarray analysis. The possibility of an additional co-occurring disorder of autism spectrum disorder (ASD) was also raised by a referring clinician. This case report highlighted the clinical dilemma of diagnosing ASD in those with existing genetic syndromes.
Keywords: developmental delay; co-occurring disorders; autism spectrum disorder